폐암으로 오인된 진행성 거대종괴성 섬유화: 두 건의 증례 보고 및 감별에 유용한 컴퓨터단층촬영 소견 - 강세리; 노지영; Se Ri Kang; Ji Young Rho (Journal of the Korean Society of Radiology, 2022)
Progressive massive fibrosis (PMF) with atypical findings is often misdiagnosed as lung cancer. Atypical features of PMF have been described in some reports; however, these reports only introduced their cases with a short literature review. We report two cases of solitary PMFs with no underlying simple pneumoconiosis or rapid growth at atypical location that were mistaken for lung cancer. We also suggest the useful CT findings to aid in the differential diagnosis. 진행성 거대종괴성 섬유화는 비정형적인 소견을 나타낼 경우 종종 폐암으로 오인된다. 현재까지 비정형적인 소견을 나타내는 진행성 거대종괴성 섬유화에 대해 몇 개의 보고가 있으나 짧은 문헌 고찰과 함께 사례를 소개했을 뿐이었다. 이에 저자들은 컴퓨터단층촬영에서 기저에 단순 진폐증이 없거나, 빠르게 커지는 비정형적 위치의 고립성 종괴로 보여 원발성 폐암으로 오인되었던 진행성 거대종괴성 섬유화 2예를 보고하고 감별에 도움이 되는 컴퓨터단층 촬영 소견을 제시하고자 한다.